Lessons from diversity of directed evolution experiments by an analysis of 3, 000 mutations. Issue 12 (14th July 2014) - Zhao, Jing; Kardashliev, Tsvetan; Joëlle Ruff, Anna; Bocola, Marco; Schwaneberg, Ulrich
ABSTRACT Diversity generation by random mutagenesis is often the first key step in directed evolution experiments and screening of 1, 000–2, 000 clones is in most directed evolution campaigns sufficient to identify improved variants. For experimentalists important questions such as how many positions are mutated in the targeted gene and what amino acid substitutions can be expected after screening of 1, 000–2, 000 clones are surprisingly not answered by a statistical analysis of mutant libraries. Therefore three random mutagenesis experiments (epPCR with a low‐ and a high‐mutation frequency and a transversion‐enriched sequence saturation mutagenesis method named SeSaM‐Tv P/P) were performed on the lipase BSLA and in total 3, 000 mutations were analyzed to determine the diversity in random mutagenesis libraries employed in directed evolution experiments. The active fraction of the population ranged from 15% (epPCR‐high), to 52% (SeSaM‐Tv P/P), and 55% (epPCR‐low) which correlates well with the average number of amino acid substitutions per protein (4.1, 1.6 and 1.1). In the epPCR libraries transitions were the predominant mutations (>72%), and >82% of all mutations occurred at A‐ or T‐nts. Consecutive nucleotide (nt) mutations were obtained only with a low fraction (2.8%) under highly error‐prone conditions. SeSaM‐Tv P/P was enriched in transversions (43%; >1.7‐fold more than epPCR libraries), and consecutive nt mutations (30.5%; 11‐fold more than epPCR‐high). A high fraction of wild‐type BSLA protein (33%) was found in the epPCR‐low mutant library compared to 2% in epPCR‐high and 13% in SeSaM‐Tv P/P. An average of 1.8–1.9 amino acid substitutions per residue was obtained with epPCR‐low and ‐high compared to 2.1 via SeSaM‐Tv P/P. The chemical composition of the amino acid substitutions differed, however, significantly from the two epPCR methods to SeSaM‐Tv P/P. Biotechnol. Bioeng. 2014;111: 2380–2389. © 2014 Wiley Periodicals, Inc.